Comparison of Candida albicans Colonies in Saliva of Elderly with and Without Diabetes - Tanaya, Angabaya Dera Sumba; Qurrohman, Muhammad Taufiq (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Diabetes mellitus is a chronic metabolic disorder that not only affects systemic organs but also influences oral health by increasing susceptibility to opportunistic infections such as oral candidiasis caused by Candida albicans. This condition is more pronounced among the elderly, whose immune functions naturally decline with age. This study aimed to compare the number of Candida albicans colonies in the saliva of elderly individuals with and without diabetes mellitus. An observational analytic study with a comparative cross-sectional design was conducted involving 32 elderly participants, consisting of 16 individuals with diabetes and 16 without. Saliva samples were collected using the passive drooling technique and cultured on CHROMagar-Candida medium for 48 hours at 37°C. The colony counts were analyzed using the Shapiro-Wilk, Levene, and Mann-Whitney U tests. The results showed that the elderly with diabetes mellitus had a significantly higher number of Candida albicans colonies compared to those without diabetes (p < 0.05). Diabetes mellitus increases the colonization of Candida albicans in the oral cavity of the elderly, likely due to hyperglycemia and age-related immune decline. Maintaining stable blood glucose levels and practicing good oral hygiene are essential preventive measures to reduce the risk of opportunistic fungal infections in this population.